The Impact of Long‐Term Tai Chi Practice on the Trust Behavior of Middle‐Aged People - Hao Hong; Xin Yu; Qiaoling Li; Bing Li; Panpan Zhang (Brain and Behavior)
ABSTRACT Purpose Trust behavior is of fundamental importance for social stability and development. Middle‐aged people, owing to their abundant social resources and extensive experience, have a significant impact through their trust behavior. However, research on enhancing their trust behavior is relatively scarce. Tai Chi, as an activity that combines physical and mental exercise characteristics, may potentially influence the trust behavior of middle‐aged people, yet direct research in this regard is lacking. The objective of this study is to explore the impact of Tai Chi on the trust behavior of middle‐aged people and its underlying neural mechanisms. Method This study recruited two groups of middle‐aged individuals as research participants. Specifically, the Tai Chi group consisted of 37 middle‐aged people with long‐term Tai Chi practice experience, while the control group comprised 29 middle‐aged individuals without any Tai Chi practice background. The behavioral performance and EEG data of the participants in both groups were recorded during their participation in the trust game. Results At the behavioral level, the trust rate of the Tai Chi group was higher than the random level (50%), and they made decisions more quickly. The event‐related potential (ERP) data revealed that there were interaction effects between the Tai Chi group and the control group in the P2 and N2 components, which are ERP indicators during the decision‐making stage. Moreover, in the feedback stage, the feedback‐related negativity (FRN) amplitude evoked in the Tai Chi group was smaller than that in the control group. Conclusion Long‐term practice of Tai Chi can enhance decision‐making speed and influence brain activity. It provides important reference for understanding the relationship between Tai Chi and the trust behavior of middle‐aged people. Although there are limitations in this study, it lays a foundation for future research.